Enhanced efficacy of direct immunochemotherapy for hepatic cancer with image-guided intratumoral radiofrequency hyperthermia. Issue 11 (30th November 2022) - Kan, Xuefeng; Zhou, Guanhui; Zhang, Feng; Ji, Hongxiu; Shin, David S; Monsky, Wayne; Zheng, Chuansheng; Yang, Xiaoming
Abstract : Background: It is still a challenge to prevent tumor recurrence post radiofrequency ablation (RFA) of medium-to-large hepatocellular carcinomas (HCC). Immunochemotherapy, a combination of immunotherapy with chemotherapy, has demonstrated a great potential in augmenting the treatment efficacy for some malignancies. In this study, we validated the feasibility of using radiofrequency hyperthermia (RFH)-enhanced intratumoral immunochemotherapy of LTX-315 with liposomal doxorubicin for rat orthotopic HCC. Methods: Different groups of luciferase-labeled rat HCC cells and rat orthotopic HCC models were treated by: (1) phosphate buffered saline; (2) RFH; (3) LTX-315; (4) RFH+LTX-315; (5) liposomal doxorubicin; (6) RFH+liposomal doxorubicin; (7) LTX-315+liposomal doxorubicin; and (8) RFH+LTX-315+liposomal doxorubicin. Cell viabilities and apoptosis of different treatment groups were compared. Changes in tumor sizes were quantified by optical and ultrasound imaging, which were confirmed by subsequent histopathology. The potential underlying biological mechanisms of the triple combination treatment (RFH+LTX-315+liposomal doxorubicin) were explored. Results: Flow cytometry and MTS assay showed the highest percentage of apoptotic cells and lowest cell viability in the triple combination treatment group compared with other seven groups (p<0.001). Tumors in this group also presented the most profound decrease in bioluminescence signal intensities and the smallest tumor volumes compared with other seven groups (p<0.001). A significant increase of CD8 + T cells, CD8 + /interferon (IFN)-γ + T cells, CD8 + /tumor necrosis factor (TNF)-α + T cells, and natural killer cells, and a significant decrease of regulatory T cells were observed in the tumors (p<0.001). Meanwhile, a significantly higher level of Th1-type cytokines in both plasma (interleukin (IL)-2, IL-12, IL-18, IFN-γ) and tumors (IL-2, IL-18, IFN-γ, TNF-α), as well as a significantly lower Th2-type cytokines of IL-4 and IL-10 in plasma and tumor were detected. Conclusions: Intratumoral RFA-associated RFH could enhance the efficacy of immunochemotherapy of LTX-315 with liposomal doxorubicin for HCC, which may provide a new strategy to increase the curative efficacy of thermal ablation for medium-to-large HCC.